Impact of prey availability and competitive interactions with hunters on the ocelot Leopardus pardalis (Linnaeus, 1758) population in Macanao Peninsula, Margarita Island, Venezuela. / Impacto de la disponibilidad de presas e interacciones competitivas con cazadores en una población de cunaguaros, Leopardus pardalis (Linnaeus, 1758), de la Península de Macanao, Isla de Margarita, Venezuela. - Abarca, María; Rodríguez, Jon Paul; Lampo, Margarita; Jędrzejewski, Włodzimierz (Anartia, 2020)
ABSTRACT Carnivores strongly depend on prey populations due to their high metabolic rates and food demands, thus the spatial distribution of carnivores is often related to prey distribution. However, human impacts often reduce carnivore populations and limit their distribution. We studied the impact of prey distribution and hunting on the unique, isolated population of the ocelot Leopardus pardalis in the Macanao Peninsula of Margarita Island. By means of camera trapping and tracking we collected records of ocelots, rabbits Sylvilagus floridanus and partridges Colinus cristatus as well as records of hunting (mostly gun cartridges and traps set for rabbits and partridges) along 20 transects in various habitats, and we documented the activities of hunters. We developed a set of multiple regression models to analyse the relative impacts of prey and hunting on the number of ocelot records and compared these models with AICc (corrected Akaike Information Criterion). The best model included only two prey variables, records of rabbits and partridges,and predicted well the spatial distribution of ocelots (R 2 = 0.56). However, the second model (R= 0.62) included the negative impact of hunting on ocelot distribution and got almost equal statistical support. We also found direct evidence of ocelots killed by hunters in retaliation for stealing prey from hunters’ traps. We conclude that for the preservation of this unique island population of ocelots it is most important to ensure effective protection of the habitats that provide prey and to control hunting. RESUMEN Los carnívoros dependen directamente de las poblaciones de sus presas debido a sus altastasas metabólicas y demanda de alimento, mientras que su distribución espacial a menudo se encuentra relacionada con la distribución de sus presas. Sin embargo, cadavez esmásfrecuenteque el impactohumanoreduzca laspoblacionesde carnívoros, limitandoasísudistribución geográfica. Se estudió el impacto sobre la distribución de las presas y cacería sobre una población aislada de Leopardus pardalis en la Península de Macanao,Isla de Margarita, Venezuela. Por medio de fototrampeo y seguimiento,se obtuvieron registros de cunaguaros, conejos (Sylvilagus floridanus) y perdices (Colinus cristatus), así como también indicios de cacería (registro de presencia de cazadores, cartuchos usados y trampas para conejos y perdices). Fueron analizadas 20 transectas en variostipos de hábitats y se documentaron las actividades de distintos cazadores. Se desarrolló un modelo de regresión múltiple para analizar el impacto relativo sobre las presas y las actividades de cacería sobre el número de registros de felinos. Estos modelos se compararon usando una rutina estadística conocida como el Criterio de Información Akaike (AICc por sussiglas en inglés).El modelo más adecuado o ajustado solo usó dos variables de presas:registros de conejos y perdices. El modelo seleccionado predijo bien la distribución espacial de los cunaguaros (R2 = 0.56). Sin embargo, se encontraron evidenciasde cazade cunaguaros, la cual es ejecutadapor cazadores enretaliaciónhacia losfelinosporrobarleslaspresasde sustrampas. Se concluye que para la preservación de esta única población insular de cunaguaros esimportante garantizarla protección efectiva de loshábitats que proporcionan las presas para estosfelinos, así como el control de la cacería.